2007
DOI: 10.1002/eji.200636933
|View full text |Cite
|
Sign up to set email alerts
|

GITR/GITRL: More than an effector T cell co‐stimulatory system

Abstract: Glucocorticoid‐induced TNFR‐related protein (GITR) is a member of the TNFR superfamily, expressed in several cells and tissues including T lymphocytes, NK cells and antigen‐presenting cells (APC). GITR activation, upon interaction with its ligand (GITRL), functions as a co‐activating signal. GITRL is mainly expressed on APC and GITR/GITRL interaction is important for the development of immune response. This review summarizes recent results about the GITR/GITRL system, focusing on the interplay between APC, eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
118
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 36 publications
2
118
0
8
Order By: Relevance
“…In recent years, their role in immunity has been expanded to DC and natural killer (NK) cells (13). Our studies identified a functional form of TNF family members that can activate its cognate receptor.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, their role in immunity has been expanded to DC and natural killer (NK) cells (13). Our studies identified a functional form of TNF family members that can activate its cognate receptor.…”
Section: Discussionmentioning
confidence: 95%
“…Important examples of the latter are CD27L, 41BBL, and glucocorticoidinduced TNF receptor ligand (GITRL) 4 , controlling various facets of the T cell response, and CD40L, providing a pivotal costimulatory signal to APCs, such as dendritic cells (DCs) and B cells (1)(2)(3)(4)(5). In accordance with these regulatory functions, the aforementioned ligands have been implicated in the development of autoimmune disease, but they also represent attractive targets for cancer immunotherapy.…”
mentioning
confidence: 99%
“…Glucocorticoid-induced TNFR (GITR) and its ligand, GITRL, are recently described members of the TNFR/ligand superfamilies and are implicated in a wide range of immune functions involving both effector and regulatory T cells (Tregs) (3)(4)(5). GITR is expressed at low levels on resting mouse and human T cells and is up-regulated upon activation of CD4 ϩ and CD8 ϩ T cells.…”
mentioning
confidence: 99%